Polylactic acid-based nanofiber membrane as well as preparation method and application thereof

Through the combination of three-layer coaxial electrospinning technology and electroactive heterostructure, an interface stereocomplex polylactic acid-based nanofiber membrane is formed, which solves the problems of weak polarity and low electroactivity of polylactic acid in air filter membranes. It realizes efficient filtration and degradable air filtration effects.

CN119318888APending Publication Date: 2025-01-17SHENHUA SHENDONG COAL GRP +4
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411626921.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Polylactic acid is difficult to maintain the electret effect due to poor crystallization effect, weak polarity and low electroactivity in the air filter membrane, which affects the filtration efficiency and environmental degradability.

Method used

Three-layer coaxial electrospinning technology is adopted, combining left-hand and dextrocyclic polylactic acid layers and electroactive heterostructure layers, through the dual action of electret and nucleating agent, an interface stereocomplex polylactic acid-based nanofiber membrane is formed. , enhance its electroactive and hydrophobicity.

Benefits of technology

It realizes high-efficiency filtration of PMs, antimicrobial activity, self-cleaning, low filtration resistance and long-term stable electroactive, improves the tensile strength and high temperature resistance of the fiber membrane, and meets the needs of degradable and high-performance air filtration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318888A_ABST
    Figure CN119318888A_ABST
Patent Text Reader

Abstract

The invention discloses a polylactic acid-based nanofiber membrane as well as a preparation method and application thereof, and belongs to the technical field of air filtering membrane materials, fibers of the polylactic acid-based nanofiber membrane provided by the invention are formed by compounding an electroactive heterostructure layer and a dextrorotation polylactic acid layer, and the electroactive heterostructure layer is formed by a levorotation polylactic acid layer, an electret and a nucleating agent. According to the polylactic acid-based nanofiber membrane prepared by the preparation method disclosed by the invention, the PMs filtering efficiency reaches 99.0%-99.99%, the surface potential is maintained at 12 kV to 18 kV, the breathing resistance is 90 Pa to 180 Pa, the antiviral efficiency is 99.0%-99.98%, and the bacteria filtering efficiency is 99.2%-99.98%. According to the invention, the electroactivity and hydrophobicity of the nanofiber membrane are enhanced by combining a polylactic acid interface stereochemical compound with an electroactive heterostructure, so that the nanofiber membrane has the characteristics of fouling resistance (microorganisms, blood, dyes and the like) and high air filtration performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air filtration membrane materials, and in particular to a polylactic acid-based nanofiber membrane and a preparation method and application thereof. Background Art

[0002] Particulate matter (PMs), especially particles with an aerodynamic diameter less than 2.5 μm (PM 2.5 ), which are easy to carry toxic and harmful substances (such as heavy metals, pathogens, etc.), and can enter the bronchi and lungs of the human body almost unhindered, thus causing respiratory infections, lung cancer and cardiovascular diseases. In order to effectively block harmful particles and protect human health, it is urgent to develop air filter membranes that can inactivate microorganisms for a long time, have low filtration resistance and excellent filtration effect.

[0003] At present, most high-efficiency air filter membranes are electrostatically charged polypropylene fibers during the melt-blown manufacturing process to make them into electrostatic electret melt-blown cloth. In addition to mechanical filtration, this filter membrane also uses the Coulomb force of charged fibers to capture particles, greatly increasing the filtration efficiency. However, polypropylene is difficult to degrade in nature, posing a huge challenge to environmental protection.

[0004] Polylactic acid is considered to be a good substitute. It is one of the most representative biodegradable materials. Polylactic acid is made from starch extracted from plants. The carbon dioxide and water produced by degradation in nature can be reused by plants through photosynthesis, which embodies a green cycle of recyclability and sustainable development. Due to its excellent mechanical properties, good biocompatibility, non-toxicity and mildness, it has broad application prospects in the field of air filtration. At the same time, polylactic acid exhibits shear triboelectricity due to the chiral center in its molecular chain. It does not require polarization treatment with an external electric field, and voltage can be generated through mechanical action. This method is simple, efficient, and easy to achieve large-scale production. However, polylactic acid has intrinsic defects such as poor crystallization effect, weak polarity, and low electroactivity, so it is not conducive to maintaining the electret effect. Summary of the invention

[0005] The invention provides a polylactic acid-based nanofiber membrane and a preparation method and application thereof, which effectively solves the technical problem that the polylactic acid has poor crystallization effect, weak polarity and low electrical activity, which is not conducive to maintaining the electret effect. The invention utilizes three-layer coaxial electrospinning stereocomposite polylactic acid, anchors a hydrophobic electret, and combines the dual effects of a polylactic acid nucleating agent to promote crystallization, thereby obtaining an interfacial stereocomposite polylactic acid-based nanofiber membrane (SIP-PLANFMs) that is degradable, has high potential, has antimicrobial activity, is hydrophobic and antifouling (all kinds of dust, blood, dyes, etc.), is self-cleaning, has excellent filtering effect on PMs, and has low filtration resistance.

[0006] The present invention provides a polylactic acid-based nanofiber membrane, wherein the fibers in the polylactic acid-based nanofiber membrane are composited by coaxial electrostatic spinning of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer and a right-handed polylactic acid layer.

[0007] In radial direction, the fiber is composed of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer and a right-handed polylactic acid layer arranged in any order; the electroactive heterogeneous structure layer is prepared using electret and a nucleating agent as raw materials.

[0008] As a preferred embodiment, the mass ratio of the electret to the nucleating agent in the electroactive heterostructure layer is 2-8:8-2; the mass ratio of the L-polylactic acid, the D-polylactic acid and the electroactive heterostructure is 1:1:0.1.

[0009] As a preferred embodiment, the fiber of the polylactic acid-based nanofiber membrane has an electroactive heterogeneous structure layer as a core layer, and a left-handed polylactic acid layer and a right-handed polylactic acid layer as a middle layer or an outer layer, respectively.

[0010] The second object of the present invention is to provide a method for preparing the above-mentioned polylactic acid-based nanofiber membrane, comprising the following steps:

[0011] L-polylactic acid and D-polylactic acid are used as raw materials and are dissolved in solvents to form a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0012] The electret and the nucleating agent are used as raw materials, mixed and crushed to obtain an electroactive heterogeneous structure, which is dispersed in a solvent to obtain a third spinning solution with a mass concentration of 1wt% to 5wt%.

[0013] The first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane.

[0014] As a preferred embodiment, the parameters of the electrospinning are: an output voltage of 25kV to 40kV, a spinning temperature of 20°C to 50°C, and a spinning humidity of 20% to 40%; during electrospinning, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 0.5mL / h to 2mL / h, and the fiber winding rate is 500rpm to 5000rpm.

[0015] As a preferred embodiment, in the electroactive heterostructure, the particle diameters of the electret and the nucleating agent are ≤100 nm.

[0016] As a preferred embodiment, the electret is one or more of nano-barium titanate, silver-doped titanium dioxide nanoparticles, titanium dioxide nanoparticles, and hydrophobic silica; the nucleating agent is one or more of ethylene bisstearamide (EBS), ethylene hydroxybisstearamide (EBH), carbon nanotubes (CNTs), and calcium carbonate (CaCO3).

[0017] As a preferred embodiment, the molecular weight of the L-polylactic acid is (1-4)×10 5 The molecular weight of dextrorotatory polylactic acid is (1~2)×10 5 The L-polylactic acid and the D-polylactic acid are dissolved in the solvent respectively and stirred for 0.5 to 2 hours.

[0018] As a preferred embodiment, the solvent is at least one of dimethyl carbonate (DMC), N-dimethylformamide (DMF), dichloromethane and chloroform.

[0019] The third object of the present invention is to provide an application of the above-mentioned polylactic acid-based nanofiber membrane in air filtration.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The fiber of the polylactic acid-based nanofiber membrane provided by the present invention is composed of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer formed by an electret and a nucleating agent, and a right-handed polylactic acid layer. By introducing an electret in the electrostatic spinning process, the electret is used to induce the self-polarization of the interface of the left-handed polylactic acid and the right-handed polylactic acid, thereby increasing the hydrogen bond density and promoting the formation of stereocomplexation, obtaining a special helical structure stereocomplexation structure, and even stereocomplexation crystals, thereby obtaining an interface stereocomplexed polylactic acid-based nanofiber membrane, i.e., a SIP-PLA fiber membrane, by anchoring a hydrophobic electret into the stereocomplexed polylactic acid, combined with the dual effect of the polylactic acid nucleating agent promoting crystallization, a polylactic acid-based nanofiber membrane is obtained. Polylactic acid has special triboelectric / piezoelectric properties. In the process of the nanofiber membrane being used, it can spontaneously supplement the charge by means of friction or relative movement in the shear direction to form an electric field, so that the electret effect of the nanofiber membrane is more durable. In addition, since the stereocomplexation process changes the polylactic acid chain structure and the degree of dipole arrangement, thereby enhancing the polarization degree of polylactic acid and changing the helical conformation of polylactic acid, the tensile strength, electrical activity and high temperature resistance of polylactic acid are greatly improved.

[0022] Compared with traditional polylactic acid fiber membranes, the polylactic acid-based nanofiber membranes prepared in the present invention are biodegradable, have high potential, antimicrobial activity, are hydrophobic and antifouling (various types of dust, blood, dyes, etc.), are self-cleaning, have a simple preparation process, have excellent filtering effects on PMs, have low filtration resistance, and long-term storage will not affect the potential of the filter material. The addition of electroactive heterogeneous structures has a significant enhancing effect on the electroactivity of polylactic acid-based nanofiber membranes (SIP-PLANFMs).

[0023] The polylactic acid-based nanofiber membrane prepared by the present invention has a filtration efficiency of 99.0% to 99.99% for PMs, a surface potential maintained at 12kV to 18kV, a respiratory resistance of 90Pa to 180Pa, an antiviral efficiency of 99.0% to 99.98%, and a bacterial filtration efficiency of 99.2% to 99.98%. The present invention strengthens the electrical activity and hydrophobicity of the nanofiber membrane by combining the polylactic acid interface stereocomplex with an electroactive heterogeneous structure, so that the fiber membrane has the characteristics of antifouling (microorganisms, blood, dyes, etc.) and high air filtration performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a process flow chart of the preparation of the polylactic acid-based nanofiber membrane of the present invention.

[0025] Figure 2 This is an electron microscope scanning image of the antifouling performance of the polylactic acid-based nanofiber membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0027] The existing polylactic acid mentioned in the background technology of the present invention has intrinsic defects such as poor self-crystallization effect, weak polarity and low electroactivity, which is not conducive to maintaining the electret effect. Based on the above technical problems, the present invention provides a polylactic acid-based nanofiber membrane and its preparation method and application.

[0028] The technical solution of the present invention is analyzed and explained in detail below.

[0029] The present invention first provides a polylactic acid-based nanofiber membrane, wherein the fibers in the polylactic acid-based nanofiber membrane are composited by coaxial electrospinning of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer and a right-handed polylactic acid layer.

[0030] In radial direction, the fiber is composed of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer and a right-handed polylactic acid layer arranged in any order; the electroactive heterogeneous structure layer is prepared using electret and a nucleating agent as raw materials.

[0031] In the above-mentioned polylactic acid-based nanofiber membrane, by introducing an electret, the electret is used to induce the interface self-polarization of left-handed polylactic acid and right-handed polylactic acid, thereby increasing the hydrogen bond density and promoting the formation of stereocomplexation, obtaining a special helical structure stereocomplexation structure, or even stereocomplexation crystal, thereby obtaining an interface stereocomplexation polylactic acid-based nanofiber membrane. In the process of using the nanofiber membrane, the charge can be spontaneously supplemented by friction or relative movement in the shear direction to form an electric field, so that the electret effect of the nanofiber membrane is more durable. Since the stereocomplexation process changes the polylactic acid chain structure and the degree of dipole arrangement, thereby strengthening the polarization degree of polylactic acid, and changing the helical conformation of polylactic acid, the tensile strength, electrical activity, and high temperature resistance of polylactic acid are greatly improved.

[0032] As a preferred embodiment, the mass ratio of the electret to the nucleating agent in the electroactive heterostructure layer is 2-8:8-2; the mass ratio of the L-polylactic acid, the D-polylactic acid and the electroactive heterostructure is 1:1:0.1. The polylactic acid nucleating agent is mainly used to deepen the depth of the electron trap. If it accounts for too much, it will affect the electret effect of the electret, that is, inhibit the generation of charge; if the number of electrets is too large and the content of the nucleating agent is insufficient, it will affect the charge generation ability of the nanofiber membrane, and the performance cannot be improved fundamentally. Therefore, the present invention obtains the above-mentioned preferred ratio through experiments.

[0033] It should be noted that heterostructure is a general term for nucleating agents and electrets. The present invention studies the ratio of heterostructures compared to L-polylactic acid and D-polylactic acid. Its proportion in the electrospinning process is regulated, and this ratio is the optimal ratio. Since the price of heterostructures is not low, continuing to increase its content will not significantly improve the performance, so the cost performance is not high; adding too little content will have a non-gaining effect on the performance, so the present invention does not further explore the mass ratio of L-polylactic acid, D-polylactic acid and electroactive heterostructures.

[0034] In order to obtain a polylactic acid-based nanofiber membrane with optimal charge retention and anti-fouling capabilities, the fibers of the polylactic acid-based nanofiber membrane have an electroactive heterogeneous structure layer as a core layer, and a left-handed polylactic acid layer and a right-handed polylactic acid layer as a middle layer or an outer layer, respectively.

[0035] The second object of the present invention is to provide a method for preparing the above-mentioned polylactic acid-based nanofiber membrane, comprising the following steps:

[0036] L-polylactic acid and D-polylactic acid are used as raw materials and dissolved in solvents respectively to obtain a first spinning solution with a mass concentration of 10wt% and a second spinning solution with a mass concentration of 10wt%.

[0037] The electret and the nucleating agent are used as raw materials, mixed and crushed to obtain an electroactive heterogeneous structure, which is dispersed in a solvent to obtain a third spinning solution with a mass concentration of 1wt% to 5wt%. If the mass concentration of the third spinning solution is too low, the expected effect cannot be achieved. If the mass concentration is too high, uneven dispersion will result in clogging of the needle and affecting the normal spinning process.

[0038] The first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane.

[0039] In order to spin to obtain fibers and fiber membranes with uniform composition, the electrospinning parameters are: output voltage of 25kV to 40kV, spinning temperature of 20℃ to 50℃, spinning humidity of 20% to 40%; during electrospinning, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 0.5mL / h to 2mL / h, and the fiber winding rate is 500rpm to 5000rpm. For the above-mentioned fiber winding rate, the winding speed mainly affects the fiber thickness and is a relatively important indicator. The fiber is thick at a low speed and thin at a high speed, but the roller cannot withstand too high a speed, so the present invention selects the above-mentioned electrospinning parameter group in the experimental exploration.

[0040] In order to ensure a better spinning effect, the particle diameter of the electret and the nucleating agent in the electroactive heterostructure is ≤100nm. Since the diameter of the spinning needle is limited, the spinning must be uniformly dispersed so that the needle will not be blocked. Less than 100nm ensures that the solution is evenly dispersed and the needle is not blocked.

[0041] As a preferred embodiment, the electret is one or more of nano-barium titanate, silver-doped titanium dioxide nanoparticles, titanium dioxide nanoparticles, and hydrophobic silica; the nucleating agent is one or more of ethylene bis stearamide (EBS), ethylene hydroxy bis stearamide (EBH), carbon nanotubes (CNTs), and calcium carbonate (CaCO3). Controlling the type of electret anchored in the electrospinning process can produce different performance changes on the fiber membrane, which is controllable. For example, electrets with silver and titanium will make the fiber membrane have an antibacterial effect, while other types of electrets have no antibacterial effect, but will not affect the characterization results of other fiber properties.

[0042] As a preferred embodiment, the molecular weight of the L-polylactic acid is (1-4)×10 5 The molecular weight of dextrorotatory polylactic acid is (1~2)×10 5The L-polylactic acid and the D-polylactic acid are dissolved in the solvent respectively and stirred for 0.5 to 2 hours. The molecular weight of the L-polylactic acid and the D-polylactic acid is greater than 100,000, and the viscosity of the spinning solution is sufficient to support the spinning process. The molecular weight range given here is the molecular weight range with the best electrospinning effect. If it is larger or smaller, the effect is not good.

[0043] As a preferred embodiment, the solvent is at least one of dimethyl carbonate (DMC), N-dimethylformamide (DMF), dichloromethane and chloroform.

[0044] The technical effects of the present invention are described in detail below through specific embodiments and comparative examples.

[0045] Example 1

[0046] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0047] S1. Preparation of spinning solution: 1 g of a molecular weight of 1×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 1×10 5 The right-handed polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of NN dimethylformamide (DMF) and dimethyl carbonate (DMC) in a volume ratio of 3:7, and stirred for 0.5 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0048] S2. Preparation of electroactive heterostructures: 0.1 g of electret nano-barium titanate and nucleating agent ethylene bisstearamide (EBS) were weighed in a mass ratio of 1:9 and crushed by a cell disruptor to make the diameter and morphology uniform.

[0049] S3, preparing the third spinning solution: dispersing the electroactive heterostructure obtained in S2 in 10 mL of dimethyl carbonate, crushing and dispersing it evenly using a cell disruptor to make it spinnable, and obtaining the third spinning solution with a mass concentration of 1 wt%.

[0050] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., EN@PLLA@PDLA nanofiber membrane, which has a gram weight of 7.5 g / m 2 , and its average fiber diameter is 2μm; during electrospinning, the output voltage is 25kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 0.5mL / h, the roller speed is 500rmp, the spinning temperature is 20℃, the spinning humidity is 20%, and the outer layer of the spun fiber is a right-handed polylactic acid layer, the middle layer is a left-handed polylactic acid, and the core layer is a heterogeneous structure layer of the third spinning solution.

[0051] Example 2

[0052] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0053] S1. Preparation of spinning solution: 1 g of molecular weight 4×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 2×10 5 The dextrorotatory polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of NN dimethylformamide (DMF) and dichloromethane in a volume ratio of 3:7, and stirred for 2 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0054] S2. Preparation of electroactive heterostructures: 0.5 g of electret titanium dioxide nanoparticles and nucleating agent ethylene hydroxybisstearamide (EBH) were weighed in a mass ratio of 9:1, and crushed by a cell disruptor to make the diameter and morphology uniform.

[0055] S3. Prepare the third spinning solution: disperse the electroactive heterostructure obtained in S2 in 10 mL of N-N dimethylformamide (DMF), use a cell disruptor to crush and disperse it evenly to make it spinnable, and obtain a third spinning solution with a mass concentration of 5 wt%.

[0056] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., PLLA@EN@PDLA nanofiber membrane, with a gram weight of 2 g / m 2 , and its average fiber diameter is 0.01μm; during electrospinning, the output voltage is 50kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 2mL / h, the roller speed is 5000rmp, the spinning temperature is 50℃, the spinning humidity is 40%, and the outer layer of the spun fiber is a right-handed polylactic acid layer, the middle layer is a heterogeneous structure layer of the third spinning solution, and the core layer is a left-handed polylactic acid.

[0057] Example 3

[0058] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0059] S1. Preparation of spinning solution: 1 g of molecular weight 2×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 1×10 5The right-handed polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of chloroform and dichloromethane in a volume ratio of 3:7, and stirred for 1.5 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0060] S2. Preparation of electroactive heterostructures: 0.4 g of electret silver-doped titanium dioxide nanoparticles and nucleating agent calcium carbonate were weighed in a mass ratio of 3:7 and crushed by a cell disruptor to make their diameter and morphology uniform.

[0061] S3, preparing the third spinning solution: dispersing the electroactive heterogeneous structure obtained in S2 in 10 mL of chloroform, crushing and dispersing it evenly using a cell disruptor to make it spinnable, and obtaining the third spinning solution with a mass concentration of 4 wt%.

[0062] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., PLLA@EN@PDLA nanofiber membrane, with a gram weight of 5 g / m 2 , and its average fiber diameter is 1.5μm; during electrospinning, the output voltage is 25kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 1mL / h, the roller speed is 3000rmp, the spinning temperature is 30℃, the spinning humidity is 25%, and the outer layer of the spun fiber is a right-handed polylactic acid layer, the middle layer is a heterogeneous structure layer of the third spinning solution, and the core layer is a left-handed polylactic acid layer.

[0063] Example 4

[0064] A method for preparing a polylactic acid-based composite film comprises the following steps:

[0065] S1. Preparation of spinning solution: 1 g of molecular weight 2×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 1×10 5 The dextrorotatory polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of chloroform and dimethyl carbonate (DMC) in a volume ratio of 3:7, and stirred for 1 hour to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0066] S2. Preparation of electroactive heterostructures: 0.25 g of electret hydrophobic silica and nucleating agent carbon nanotubes (CNTs) were weighed in a mass ratio of 1:1, and crushed by a cell disruptor to make their diameter and morphology uniform.

[0067] S3, preparing the third spinning solution: dispersing the electroactive heterostructure obtained in S2 in 10 mL of dichloromethane, crushing and dispersing it evenly using a cell disruptor to make it spinnable, and obtaining the third spinning solution with a mass concentration of 2.5 wt%.

[0068] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., EN@PDLA@PLLA nanofiber membrane, which has a gram weight of 4 g / m 2 , and its average fiber diameter is 1 μm; during electrospinning, the output voltage is 25 kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 1 mL / h, the roller speed is 1000 rpm, the spinning temperature is 30°C, the spinning humidity is 25%, and the outer layer of the spun fiber is the heterogeneous structure layer of the third spinning solution, the middle layer is right-handed polylactic acid, and the core layer is a left-handed polylactic acid layer.

[0069] Example 5

[0070] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0071] S1. Preparation of spinning solution: 1 g of a molecular weight of 1×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 1×10 5 The right-handed polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of NN dimethylformamide (DMF) and dimethyl carbonate (DMC) in a volume ratio of 3:7, and stirred for 0.5 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0072] S2. Preparation of electroactive heterostructures: 0.1 g of electret nano-barium titanate and nucleating agent ethylene bisstearamide (EBS) were weighed in a mass ratio of 1:9 and crushed by a cell disruptor to make the diameter and morphology uniform.

[0073] S3, preparing the third spinning solution: dispersing the electroactive heterostructure obtained in S2 in 10 mL of dimethyl carbonate, crushing and dispersing it evenly using a cell disruptor to make it spinnable, and obtaining the third spinning solution with a mass concentration of 1 wt%.

[0074] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., EN@PDLA@PLLA nanofiber membrane, which has a gram weight of 7.5 g / m 2, and its average fiber diameter is 2μm; during electrospinning, the output voltage is 25kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 0.5mL / h, the roller speed is 500rmp, the spinning temperature is 20℃, the spinning humidity is 20%, and the outer layer of the spun fiber is a left-handed polylactic acid layer, the middle layer is a right-handed polylactic acid, and the core layer is a heterogeneous structure layer of the third spinning solution.

[0075] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:

[0076] Comparative Example 1

[0077] Compared with Example 1, the difference is that: instead of using a three-layer coaxial electrospinning method, the first spinning solution, the second spinning solution and the third spinning solution are directly mixed and co-spun by a single needle to obtain a polylactic acid-based nanofiber membrane.

[0078] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0079] S1. Preparation of spinning solution: 1 g of a molecular weight of 1×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 1×10 5 The right-handed polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of NN dimethylformamide (DMF) and dimethyl carbonate (DMC) in a volume ratio of 3:7, and stirred for 0.5 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0080] S2. Preparation of electroactive heterostructures: 0.1 g of electret nano-barium titanate and nucleating agent ethylene bisstearamide (EBS) were weighed in a mass ratio of 1:9 and crushed by a cell disruptor to make the diameter and morphology uniform.

[0081] S3, preparing the third spinning solution: dispersing the electroactive heterostructure obtained in S2 in 10 mL of dimethyl carbonate, crushing and dispersing it evenly using a cell disruptor to make it spinnable, and obtaining the third spinning solution with a mass concentration of 1 wt%.

[0082] S4. Preparation of polylactic acid-based nanofiber membrane: The first spinning solution, the second spinning solution and the third spinning solution are mixed and single-needle co-spinned. During electrospinning, the output voltage is 25 kV, the consumption rate of the first spinning solution, the second spinning solution and the third spinning solution are all 0.5 mL / h, the roller speed is 500 rpm, the spinning temperature is 20 ° C, the spinning humidity is 20%, and the polylactic acid-based nanofiber membrane is obtained, which has a gram weight of 7.5 g / m 2 , and its average fiber diameter is 2μm.

[0083] Comparative Example 2

[0084] Compared with Example 2, the difference is that instead of using electret as filler, only nucleating agent is used as filler, and ordinary "shell-core-shell" structured polylactic acid-based nanofiber membrane is prepared by three-layer coaxial electrospinning.

[0085] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0086] S1. Preparation of spinning solution: 1 g of molecular weight 4×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 2×10 5 The dextrorotatory polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of NN dimethylformamide (DMF) and dichloromethane in a volume ratio of 3:7, and stirred for 2 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0087] S2. Preparation of electroactive heterostructures: Weigh 0.5 g of nucleating agent ethylene hydroxybisstearamide (EBH), and crush it with a cell disruptor to make its diameter and morphology uniform.

[0088] S3. Prepare the third spinning solution: disperse the electroactive heterostructure obtained in S2 in 10 mL of N-N dimethylformamide (DMF), use a cell disruptor to crush and disperse it evenly to make it spinnable, and obtain a third spinning solution with a mass concentration of 5 wt%.

[0089] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., PLLA@EN@PDLA nanofiber membrane, with a gram weight of 2 g / m 2 , and its average fiber diameter is 0.01μm; during electrospinning, the output voltage is 50kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 2mL / h, the roller speed is 5000rmp, the spinning temperature is 50℃, the spinning humidity is 40%, and the outer layer of the spun fiber is a right-handed polylactic acid layer, the middle layer is a heterogeneous structure layer of the third spinning solution, and the core layer is a left-handed polylactic acid layer.

[0090] Comparative Example 3

[0091] Compared with Example 3, the difference is that no nucleating agent is used as filler, but only electret is used as filler, and a polylactic acid-based nanofiber membrane with a common "shell-core-shell" structure is prepared by three-layer coaxial electrospinning.

[0092] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0093] S1. Preparation of spinning solution: 1 g of molecular weight 2×10 5 The molecular weight of 1g of polylactic acid (PLLA) is 1×10 5 The right-handed polylactic acid (PDLA) was dissolved in 10 mL of a mixed solution of chloroform and dichloromethane in a volume ratio of 3:7, and stirred for 1.5 h to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%.

[0094] S2. Preparation of electroactive heterostructures: Weigh 0.4 g of electret silver-doped titanium dioxide nanoparticles and crush them with a cell disruptor to make their diameter and morphology uniform.

[0095] S3, preparing the third spinning solution: dispersing the electroactive heterogeneous structure obtained in S2 in 10 mL of chloroform, crushing and dispersing it evenly using a cell disruptor to make it spinnable, and obtaining the third spinning solution with a mass concentration of 4 wt%.

[0096] S4, preparation of polylactic acid-based nanofiber membrane: the first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane, i.e., PLLA@EN@PDLA nanofiber membrane, with a gram weight of 5 g / m 2 , and its average fiber diameter is 1.5μm; during electrospinning, the output voltage is 25kV, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 1mL / h, the roller speed is 3000rmp, the spinning temperature is 30℃, the spinning humidity is 25%, and the outer layer of the spun fiber is a right-handed polylactic acid layer, the middle layer is a heterogeneous structure layer of the third spinning solution, and the core layer is a left-handed polylactic acid layer.

[0097] The properties of the polylactic acid-based nanofiber membranes prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 3 were characterized and tested, and the results are as follows.

[0098] Structural characterization and performance testing:

[0099] Scanning electron microscopy: The microstructure of the PLA fiber membrane and the silver nanofiber membrane was observed by field emission scanning electron microscopy (model JSM-7900F, JEOL).

[0100] Dielectric constant test: The dielectric constant was tested using a dielectric constant tester (model Wayne Kerr 6500B, Wayne Kerr, UK).

[0101] Antimicrobial activity test: The microbial indicators indicated in GB19083-2010 "Medical Protective Masks" are used for testing. The standards are: Staphylococcus aureus, coliform bacteria, Pseudomonas aeruginosa, hemolytic streptococci and fungal colonies shall not be detected, and the total bacterial colony count shall not exceed 20 CFU / g; YY 0469-2011 "Technical Requirements for Medical Surgical Masks" The bacterial filtration efficiency shall not be less than 95%.

[0102] Antiviral test: The antiviral performance of textiles finished with high-efficiency antiviral fibers was tested using the method provided by ISO 18184:2019 "Test Standard for Antiviral Textiles". The antiviral efficiency of the material can be obtained by comparing the number of viruses on the blank control sample and the sample after contact with the virus (influenza virus H1N1 and coronavirus HCov-229E) for 2 hours. The virus used in the present invention is coronavirus HCov-229E.

[0103] Respiratory resistance test: A micromanometer (AIRPROAP800, TSI, USA), anthropomorphic respirator and simulated human head were used to measure respiratory resistance. The gas flow rate was set to 85L / min, and the filter membrane was encapsulated on the simulated human head. The air pressure of the cavity formed by the filter membrane and the human head and the atmospheric pressure were measured and the difference was made. The experiment was repeated three times and the average value was taken to calculate the respiratory resistance of the filter membrane.

[0104] Surface potential test: A non-contact electrostatic meter (VM54XQS, Quatek, USA) was used to test the surface potential of the nanofiber membrane. The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.

[0105] Filtration performance test: The air filtration performance of the fiber membrane (area 113.04 cm2) was tested using an LZC-K automatic filter membrane tester (Suzhou Huada Instrument Equipment Co., Ltd.), with the gas flow rate set to 85 L / min and the particle size range of the NaCl atomized particles produced by the aerosol generator being 0.1-10 μm. At least three different positions were tested for each group of fiber membranes, and the average value was taken.

[0106] Antifouling performance test: The removal efficiency of dyes, blood, and PMs was measured by a qualitative method of cyclic water washing and electron microscope scanning. Three cyclic tests were performed in each group, and the results were averaged. The electron microscope scanning image of the interfacial stereocomposite polylactic acid self-cleaning air filtration nanofiber membrane after five washings is shown in the figure below. Figure 2 shown.

[0107] Table 1 Test results of respiratory resistance, surface potential and filtration performance of interfacial stereocomposite polylactic acid self-cleaning air filtration nanofiber membrane

[0108]

[0109] Table 2 Antiviral test results of interfacial stereocomposite polylactic acid self-cleaning air filtration nanofiber membrane

[0110]

[0111]

[0112] Table 3 The test results of microbial inactivation of the interfacial stereocomposite polylactic acid self-cleaning air filtration nanofiber membrane of the present invention

[0113]

[0114] Table 4 Antifouling test results of interfacial stereocomposite polylactic acid self-cleaning air filtration nanofiber membrane

[0115]

[0116] The polylactic acid-based nanofiber membrane prepared by the present invention was subjected to tests such as surface potential test, filtration efficiency test, respiratory resistance test, antiviral test, antibacterial test, filtration efficiency, and antifouling test. The results are shown in Tables 1 to 4. The polylactic acid-based nanofiber membrane prepared by the present invention (except Example 4) has a filtration efficiency of 99.0% to 99.99% for PMs, a surface potential maintained at 12 to 23 kV, a respiratory resistance of 98 to 100 Pa, an antiviral efficiency of 99.0% to 99.89%, a bacterial filtration efficiency of up to 99.99%, a filtration efficiency for pollutants greater than 99%, and a water contact angle greater than 140°.

[0117] The experiment took 5 groups of embodiments and 3 groups of comparative examples, and the relevant changes of the experimental results when the experimental conditions were changed were explained by the examples. The results showed that the simultaneous presence of electret and nucleating agent can effectively increase the charge storage capacity and antifouling ability of polylactic acid-based nanofiber membrane, and placing the electroactive heterogeneous structure in the core layer can deepen the degree of stereocomplexation. The best performance was achieved in the four groups of embodiments (Example 1 and Example 5). The embodiment with the best performance of the present invention can maintain the surface potential at about 22kV, and the amount of electricity does not change much within 30 days; adding antibacterial fillers can greatly increase the antibacterial effect of the filter membrane. The filter membrane prepared according to the present invention can maintain the bacterial filtration efficiency at 99.0%-99.89%, and the antiviral efficiency can reach 99.99%. In addition to the poor antibacterial and antiviral effects of Example 4 without adding antibacterial fillers, the other experimental tests also have considerable performance. Therefore, the experimental conditions changed in the four groups of embodiments will not have a great impact on the experimental results, that is, the experiment is feasible.

[0118] In the three groups of comparative examples, the three-layer coaxial electrospinning method, the electret as the interface filler, and the nucleating agent as the interface filler were not used to make experimental comparisons. The results showed that the electret effect would dissipate if the three-coaxial electrospinning was not used, resulting in a decrease in the charge storage capacity, which was reflected in the surface point test and significantly reduced the filtration efficiency. The stereocomplex crystallization performance of the sample without the nucleating agent would be significantly reduced, the proportion of the active component of polylactic acid would be reduced, the electret performance would be reduced, the charge dissipation would be aggravated, and the surface potential would be significantly reduced within 30 days. This also had a great impact on the hydrophobic performance because the polarization degree of the fiber surface was weak, which made it easier for water to overcome the surface tension and adhere to the fiber surface, reducing the water contact angle. The performance of the sample without the electret was more significantly reduced. The electret is a key component of fiber modification, which can effectively change the problem of disordered arrangement and weak polarity of the polylactic acid dipole. Using only the nucleating agent as a filler cannot meet the charge loss in the working engineering of the polylactic acid nanofiber membrane, resulting in a significant decrease in performance and failure to meet the standard requirements.

[0119] According to the comprehensive analysis of the embodiments and comparative examples, the polylactic acid-based nanofiber membrane with interfacial stereocomplexation has significantly improved the filtration efficiency of PMs and bacteria, the inactivation ability of viruses, and the antifouling ability compared with the traditional polylactic acid filter membrane, and significantly improved the surface potential of the filter membrane and significantly reduced the respiratory resistance. Therefore, the experimental method proposed in the present invention is feasible and the product produced meets expectations, and the materials used are reasonable, so the present invention provides a high-performance air filtration membrane with broad application prospects.

[0120] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A polylactic acid-based nanofiber membrane, characterized in that: The fibers in the polylactic acid-based nanofiber membrane are composited by coaxial electrospinning of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer and a right-handed polylactic acid layer; In radial direction, the fiber is composed of a left-handed polylactic acid layer, an electroactive heterogeneous structure layer and a right-handed polylactic acid layer arranged in any order; the electroactive heterogeneous structure layer is prepared using electret and a nucleating agent as raw materials.

2. The polylactic acid-based nanofiber membrane according to claim 1, characterized in that: The mass ratio of the electret to the nucleating agent in the electroactive heterostructure layer is 2-8:8-2; the mass ratio of the left-handed polylactic acid, the right-handed polylactic acid and the electroactive heterostructure is 1:1:0.

1.

3. The polylactic acid-based nanofiber membrane according to claim 1, characterized in that: The fiber has an electroactive heterogeneous structure layer as a core layer, and a left-handed polylactic acid layer and a right-handed polylactic acid layer as a middle layer or an outer layer respectively.

4. A method for preparing a polylactic acid-based nanofiber membrane according to any one of claims 1 to 3, characterized in that: The following steps are involved: Using left-handed polylactic acid and right-handed polylactic acid as raw materials, respectively dissolving them in solvents to obtain a first spinning solution with a mass concentration of 10 wt% and a second spinning solution with a mass concentration of 10 wt%; Using electret and nucleating agent as raw materials, mixing and grinding to obtain electroactive heterogeneous structure, dispersing in solvent, and obtaining third spinning solution with mass concentration of 1wt% to 5wt%; The first spinning solution, the second spinning solution and the third spinning solution are subjected to three-layer coaxial electrospinning to obtain a polylactic acid-based nanofiber membrane.

5. The preparation method according to claim 4, characterized in that: The parameters of the electrospinning are: output voltage of 25kV to 40kV, spinning temperature of 20°C to 50°C, spinning humidity of 20% to 40%; during electrospinning, the consumption rates of the first spinning solution, the second spinning solution and the third spinning solution are all 0.5mL / h to 2mL / h, and the fiber winding rate is 500rpm to 5000rpm.

6. The preparation method according to claim 4, characterized in that: In the electroactive heterostructure, the particle diameters of the electret and the nucleating agent are ≤100 nm.

7. The preparation method according to claim 4, characterized in that: The electret is one or more of nano-barium titanate, silver-doped titanium dioxide nanoparticles, titanium dioxide nanoparticles, and hydrophobic silicon dioxide; the nucleating agent is one or more of ethylene bisstearamide, ethylene hydroxybisstearamide, carbon nanotubes, and calcium carbonate.

8. The preparation method according to claim 4, characterized in that: The molecular weight of the L-polylactic acid is (1-4)×10 5 The molecular weight of dextrorotatory polylactic acid is (1~2)×10 5 The L-polylactic acid and the D-polylactic acid are dissolved in the solvent respectively and stirred for 0.5 to 2 hours.

9. The preparation method according to claim 4, characterized in that: The solvent is at least one of dimethyl carbonate, N-N-dimethylformamide, dichloromethane and chloroform.

10. Use of the polylactic acid-based nanofiber membrane according to any one of claims 1 to 3 in air filtration.

Citation Information

Cited By

  • Charged polylactic acid non-woven fabric as well as preparation method and application thereof

    CN120683654A